Interview: Molecular neuro-oncology: a forward-looking perspective - O'Neill, Tess (CNS Oncology, 2013)
Wolfgang Wick is the Chairman of the Department of Neuro-Oncology, Hertie Professor of Neuro-Oncology and Director at the National Tumor Center at the University of Heidelberg, Germany. He is conducting multicenter Phase III randomized trials for the Neuro-Oncology Working Group of the German Cancer Society, the European Organisation for Research and Treatment of Cancer as well as a number of multicenter trials with the pharmaceutical industry. He is a steering committee member of the Neuro-Oncology Working Group and the European Association for Neuro-oncology as well as chairman of the European Organisation for Research and Treatment of Cancer Brain Tumor Group. His main scientific interests include migration and invasion of glioma cells, biomarkers and radiosensitization.
Gesehen am 04.11.2021